Technical Efficiency of Indonesian Sharia Banks: A Data Envelopment Analysis Approach - Ulkhaq, M. Mujiya (Department of Islamic Accounting, The Faculty of Islamic Economics and Business, State Islamic Institute of Kediri [IAIN Kediri, 2023)
The existence of competition among sharia banks is one of the effects that occur with the development of sharia banks. The purpose of this study is to analyze the efficiency of Sharia banks in Indonesia. Understanding efficiency is important because if banks are always operating at full efficiency, the fewer inputs they use, the greater the output they achieve. Output is measured by total earning assets, while the inputs used are total deposits and total operating expenses. A data envelopment analysis with input-oriented and variable returns to scale is used to achieve the objective. The result shows that of the twelve Sharia banks studied, four are considered to be the most efficient. Adanya persaingan antar bank syariah merupakan salah satu dampak yang terjadi dengan berkembangnya bank syariah. Tujuan dari penelitian ini adalah untuk menganalisis efisiensi bank syariah di Indonesia. Memahami efisiensi menjadi penting karena jika bank selalu beroperasi pada tingkat efisiensi penuh, maka semakin sedikit input yang mereka gunakan, semakin besar output yang mereka capai. Output diukur dengan total aktiva produktif, sedangkan input yang digunakan adalah total simpanan dan total biaya operasional. Untuk mencapai tujuan tersebut, digunakan analisis data envelopment dengan pendekatan input-oriented dan variable returns to scale. Hasilnya menunjukkan bahwa dari dua belas bank syariah yang diteliti, empat bank dianggap paling efisien.